Enhancing Network Security with Quantum Cryptography:A Study on Future-Proofing Computer Networks AgainstQuantum Attacks - Supriati, Ruli; Purwanti; Anjani, Sheila Aulia; Anugrah, Rio Wahyudin; McCarthy, Ryan (Pandawan Sejahtera Indonesia, 2025)
The rapid development of quantum computing presents a significant challenge to existing cryptographic systems, such as RSA and Elliptic Curve Cryptography, which rely on the complexity of mathematical problems for security. Shor’s algorithm, which can efficiently solve these problems, emphasizes the need for cryptographic solutions that are resistant to quantum threats. This study aims to investigate the potential of Quantum Cryptography, with a specific focus on Quantum Key Distribution (QKD), to strengthen network security in response to emerging quantum computing risks. Despite the theoretical potential of QKD, there remains a gap in its practical application, particularly in terms of scalability, high implementation costs, and sensitivity to environmental factors, which have hindered its widespread adoption. The novelty of this research lies in the comprehensive approach it takes, combining theoretical analysis of QKD protocols, simulations using Qiskit, and comparisons with traditional cryptographic methods. This provides a more robust understanding of QKD effectiveness in different network scenarios. The study reveals that the BB84 protocol consistently outperforms the E91 protocol in terms of key generation efficiency and noise resilience. However, despite its unmatched security capabilities, QKD faces challenges such as scalability and implementation costs. To overcome these challenges and achieve widespread adoption, integrating QKD with post quantum cryptography and developing hybrid approaches are essential. Quantum Cryptography, particularly QKD, holds the potential to become a cornerstone for securing critical infrastructure, ensuring communication security in the quantum era.